2010
DOI: 10.1017/s0033291710001030
|View full text |Cite
|
Sign up to set email alerts
|

Executive functions are impaired in adolescents engaging in non-suicidal self-injury

Abstract: This study demonstrates that NSSI subgroups have distinct deficits in EFs. The high-severity NSSI group has working memory deficits, while the low-severity NSSI group has impaired inhibitory control. This supports the emotion regulation hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 43 publications
(81 reference statements)
4
57
3
Order By: Relevance
“…Westheide and colleagues also showed no association between delayed alternation and impairments in selective attention with repetition (Westheide et al, 2008). However, Miranda et al found that impairments in cognitive flexibility on the Wisconsin Card Sorting Test did predict future suicidal ideation on a background of previous self-harm (Miranda et al, 2012), and Fikke et al found an association between impaired frontal functioning and selfharm not related to specific diagnosis using set-shifting tasks (Fikke et al, 2011).…”
Section: Cognitive Controlmentioning
confidence: 99%
“…Westheide and colleagues also showed no association between delayed alternation and impairments in selective attention with repetition (Westheide et al, 2008). However, Miranda et al found that impairments in cognitive flexibility on the Wisconsin Card Sorting Test did predict future suicidal ideation on a background of previous self-harm (Miranda et al, 2012), and Fikke et al found an association between impaired frontal functioning and selfharm not related to specific diagnosis using set-shifting tasks (Fikke et al, 2011).…”
Section: Cognitive Controlmentioning
confidence: 99%
“…Glenn and Klonsky (2010) found no differences in response inhibition between participants who self-injured and those who did not. Fikke et al (2011) reported that adolescents engaging in "low-severity" NSSI were poorer at inhibiting initiated responses compared to those engaging in "high-severity" NSSI, but both groups performed comparably to healthy controls. Notably, no previous research has directly assessed inhibitory control over emotional responses among people who self-injure, an omission that may partially explain mixed findings in this literature.…”
Section: Introductionmentioning
confidence: 95%
“…Only two studies have examined inhibitory control specifically in people who self-injure (Glenn and Klonsky, 2010;Fikke et al, 2011), employing the Stop Signal Task (SST; to assess behavioral response inhibition. On each trial in this task, participants are presented with either a right-or left-facing arrow, and must quickly press the button that corresponds to the direction of the stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…It is also clear that NSSI is an international phenomenon, having been studied in Turkey [21], Hong Kong [25,26], Singapore [27], Austria [19], Belgium [28], Germany [17,18,19], Italy [29,30], the Netherlands [30], Switzerland [19], Hungary [31], Norway [32], Sweden [33], Iceland [34] and Australia [23,35], in addition to the USA and Canada.…”
Section: Prevalence Of Nssimentioning
confidence: 99%